Correlation Between TIMI Risk Score and the Number of Vessels Involved in the Angiographic Study; a Cross-sectional Study - Namazi, Mohammad Hasan; Mazloomi, Seyedeh Slimeh; Kalate Aghamohammadi, Mohammad (Archives of Academic Emergency Medicine, 2022)
Introduction: TIMI (Thrombolysis in Myocardial Infarction) score is a model for predicting the severity of vascular diseases. This study aimed to evaluate the correlation between this score and the number of vessels involved in patients with Unstable Angina (UA) or Non-ST Elevation Myocardial Infarction (NSTEMI). Methods: This prospective cross-sectional study was designed to evaluate the correlation between TIMI score, and the number of vessels involved in the angiographic study of NSTEMI and UA patients presenting to emergency department. Results: 297 patients with the mean age of 62.16±36.59 years were entered (58.2% male; 193 (65%) UA and 104 (35%) NSTEMI). The Mean TIMI score among patients was 3.21±1.55. Based on the TIMI score, patients were categorized into 3 groups. 105 (35.35%) patients had a TIMI score of 0 to 2, 120 (40.40%) had a score of 3 to 4, and 72 (24.24%) had a score of 5 to 7. Patients with a TIMI score of 5 to 7 had a greater likelihood of three-vessel coronary artery disease compared to patients with a TIMI score of 3 to 4 (OR: 5.34, 95% CI: 2.64 to 10.80; p < 0.0001) or those with a TIMI score of 0 to 2. (OR: 29.45, 95% CI: 12.87 to 67.37; p < 0.0001). Two-vessel coronary artery disease was more likely to be found in patients with a TIMI score of 3 to 4 or those with a score of 5 to 7 compared to patients with a TIMI score of 0 to 2 (OR: 3.69, 95% CI: 1.60 to 8.51; p <0.0001 and OR: 2.67, 95% CI: 1.04 to 6.82; p = 0.04, respectively). Conclusion: There is a direct and significant correlation between TIMI score and the number of coronary vessels involved in patients presenting to emergency department following UA or NSTEMI.